Business management and competitiveness of exporting smes in the peruvian textile industry - Quiroz-Flores, Juan Carlos (2024)
The objective of this research was to design an operational management model for garment exporting SMEs to increase the level of competitiveness in the international market through a structural analysis in garment exporting SMEs. The methodology used in this research was the deductive method, the scope of the study was descriptive because it is oriented to determine the factors that affect the increase of competitiveness in the international market, by means of a structural equation model of the SMEs exporting garments. The factors that affect the international competitiveness of SMEs are: Operational management, production management, supply and distribution management, human and financial resources management. The results obtained in the research support the importance of implementing an effective operational management model to improve the competitiveness of these companies in the international arena.